2021
DOI: 10.1002/est2.253
|View full text |Cite
|
Sign up to set email alerts
|

Energy storage and reuse in biological systems: Case studies

Abstract: The consequences of energy storage in the body as fat and then reusing it in the metabolism are assessed for seven cases by referring to entropy generation as the criterion for assessment: Case 1: Glycogen and lipids are stored by a person by dieting and then reused. Case 2: Glucose is converted into fat and then reconverted it into glucose spontaneously. Case 3: 2400 kcal of high-fat diet induced fatty liver disease and then a low-fat diet is consumed to recover. Case 4: Intermittent fasting by skipping a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…During cold exposure, an 80.7 kg healthy man metabolizes 0.0016 mol/24 hours glucose depending on BAT activity. The amount of heat may be calculated by using Equation (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During cold exposure, an 80.7 kg healthy man metabolizes 0.0016 mol/24 hours glucose depending on BAT activity. The amount of heat may be calculated by using Equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…If an organism cannot get sufficient energy to survive, and export entropy it will cease to exist. 1 Assessing energy utilization and storage and entropy generation 2 behavior may indicate the differences between healthy and unhealthy organisms and offer remedies to treat the morbidities. [3][4][5][6] In the present study, species-specific biological energy storage and reuse will be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study should be interpreted with caution, in case of sarcopenia or famine human body may consume its own building blocks in its energy metabolism and such an experience do not extend the lifespan. On the other hand, Ulu et al [59] showed that intermittent caloric restriction via skipping a meal for 30 days in a year without increasing the caloric content of other meals might extend the life span approximately 3%. A high-entropy generation process shortens the expected longevity more than a low-entropy generation process, as evidenced in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…Energy, e.g., enthalpy, extracted from carbohydrates will not be affected by lactic acid accumulation and its reuse in the muscles, since enthalpy is a state function and its value depends on the initial, carbohydrates and the oxygen, and the final chemical species, e.g., carbon dioxide and water ( 45 ) . Ulu et al ( 46 ) , while discussing energy storage and reuse in biological systems, reported that entropy generation associated with this phenomenon is extremely small and does not contribute to the lifespan entropy accumulation; therefore, entropy generation during lactic acid utilisation and reuse in the muscles is neglected.…”
Section: Methodsmentioning
confidence: 99%